A Researcher’s Story of Assessing Motor Skills of Children with Autism Spectrum Disorder - Breslin, Casey M.; Buchanan, Alice M. (Journal of the American Academy of Special Education Professionals, 2014)
The purpose of this study was to explore and interpret a researcher’s experiences while conducting motor skill assessments of children with autism spectrum disorder (ASD). The first author and participant-researcher was, at the time of the study, a kinesiology doctoral candidate studying motor behavior. The second author, an associate professor of kinesiology, was the interviewer. Data were captured through interviews, transcribed, and analyzed by bracketing, constructing, and contextualizing (Denzin, 1989). The three major themes that emerged were Participant Emotions, Research Protocols, and Children’s Behavior. The participant-researcher experienced enjoyment and frustration for the research process, and sympathized with the children. A second theme matched the three protocols in the dissertation: traditional-full sentences, picture schedule, and task cards. Finally, a third theme addressed her perceptions of children’s behaviors.